Development of standardised programme content for phase II cardiac rehabilitation programmes in Australia using a modified Delphi process - Cartledge, Susie (BMJ Open, 2019)
OBJECTIVE: To develop standardised programme content for Australian phase II cardiac rehabilitation (CR) programme. DESIGN: Using the RAND/UCLA appropriateness method (RAM), a two-phase process including a comprehensive literature review and a two round modified Delphi process was undertaken to develop and validate content of a standardised CR programmes. PARTICIPANTS: An invited multidisciplinary expert advisory group (EAG; n=16), including CR health professionals (nurses, allied health professionals, cardiologist), academics, policy makers, representation from the Australian Cardiovascular Health and Rehabilitation Association and consumers, provided oversight of the literature review and assisted with development of best practice statements. Twelve members of the EAG went onto participate in the modified Delphi process rating the necessity of statements in two rounds on a scale of 1 (not necessary) to 9 (essential). MAIN OUTCOME MEASURE: Best practice statements that achieved a median score of ≥8 on a nine-point scale were categorised as ‘essential’; statements that achieved a median score of ≥6 were categorised as ‘desirable’ and statements with a median score of <6 were omitted. RESULTS: 49 best practice statements were developed from the literature across ten areas of care within four module domains (CR foundations, developing heart health knowledge, psychosocial health and life beyond CR). At the end of a two-round validation process a total of 47 best practice statements were finalised; 29 statements were rated as essential, 18 as desirable and 2 statements were omitted. CONCLUSIONS: For the first time in Australia, an evidence-based and consensus-led standardised programme content for phase II CR has been developed that can be provided to CR coordinators.